Composing using Sibelius music notation software among undergraduate student of composition / Muhammad Abdullah Mohd Fazli and Muhammad Daniel Haikal Kamaruddin - Mohd Fazli, Muhammad Abdullah; Kamaruddin, Muhammad Daniel Haikal (2020)
The purpose of this study is to contribute to the readers of the knowledge on using Sibelius notation software in the correct manner and also to find the effectiveness of using Sibelius as a technology-based learning tool for composing. This research may be helpful for those who want to explore the topic in depth and further strengthen their knowledge regarding Sibelius notation software. The primary source of this research was by conducting interviews with composition students themselves hence the findings exhibited the responses of the students on how frequent do they utilize the Sibelius software for composing and individual endorsement towards their skills and musicality. The authors believe that this research can serve as guidance for composition students on pros and cons of using Sibelius as their aiding tool in composing and expand their creativity in terms of music theories and skills.